University–industry cooperation: A taxonomy of intermediaries - Santos, T.; Dias, J. G.; Mendonça, S. (Science and Public Policy, 2023)
The fragmentation of the literature on intermediaries between the university and industry has led to a disorganised and confused theoretical landscape. This research addresses this gap in the literature by proposing an analytical tool that can be used as guidance. For this purpose, this work provides a taxonomy of these intermediaries and classifies them into five different classes. To this end, we review 125 studies on university–industry cooperation (UIC) intermediaries. In addition to the general and innovation-related information, we extracted specific data related to the relevant UIC intermediaries from each article, i.e. the type(s) of intermediary addressed and its identified functions. This taxonomy is based on twenty-two functions identified in the UIC intermediary literature and thirteen UIC intermediary types. The five proposed classes of intermediaries are specialised in five different roles. This integrative background can be applied in future research and in the definition of policy-based guidelines.